2005
DOI: 10.1016/j.jmwh.2004.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Presidential Priorities: 50 Years of Wisdom as the Basis of an Action Agenda for the Next Half‐Century

Abstract: Each of the living presidents of the American College of Nurse-Midwives (ACNM), past and current, was asked to select one or more issues that were of particular importance during her term(s) in office. Some of the issues identified by the presidents were amenable to review using existing quantitative data; this article presents those findings. The substantial increase in growth of ACNM membership in the 1980s and 1990s as well as the plateau that occurred at the beginning of the 21st century is documented. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Both bodies of literature reported that the inclusion of members in policy decisions and actions ensured selected policy issues had meaning for the public served [26,48,76,[90][91][92] and for members [16,36,37,85,86,90,92,93]. Members were also viewed as critical to the work accomplished by organizations, as they served as champions for their organizations' cause(s) [48,82,94].…”
Section: Factors Influencing Priority Setting and Policy Advocacymentioning
confidence: 99%
See 2 more Smart Citations
“…Both bodies of literature reported that the inclusion of members in policy decisions and actions ensured selected policy issues had meaning for the public served [26,48,76,[90][91][92] and for members [16,36,37,85,86,90,92,93]. Members were also viewed as critical to the work accomplished by organizations, as they served as champions for their organizations' cause(s) [48,82,94].…”
Section: Factors Influencing Priority Setting and Policy Advocacymentioning
confidence: 99%
“…In these cases, organizations reacted by taking action for a new policy or changing their course of action [36,65,85,92]. Environmental catastrophes, such as oil spills, instigated changes in beliefs, values, rules, and players leading to opportunities to address new or emerging policy issue [60].…”
Section: System Disruptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the profession faces a renewed challenge to their control of how midwifery is to be defined and practiced and to how midwives will be educated. This concern has already been clearly identified elsewhere in this issue 8,22 . But midwives today also confront a challenge to the normalcy of birth, and this challenge, too, requires the kind of energy, creativity, and determination that saw midwives through many similar crises in the past.…”
Section: Future Challengesmentioning
confidence: 87%
“…Thus, nurse‐midwives had to learn fundamentals of pharmacology and details about the newest relevant drugs. The growth of prescriptive privileges by midwives is detailed in an accompanying article by Fullerton et al 8 …”
mentioning
confidence: 99%